Global Environment Security : Role of Tropical Forest Therein - Soni, P.; Vasistha, H. B.; Kumar, Om (Indian Forester, 1992)
The paper summarizes the changing pattern of environmental degradation, identifies causes of these catastrophes and discusses the role of tropical forests in ensuring the global environmental security. Steps have been suggested which will assist in protection, preservation, conservation and afforestation of tropical forests. Need to have a partnership of developed countries in preserving the global environment an regreenlng of the earth has been stressed.